IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN KEBUDAYAAN, RISET, DAN TEKNOLOGI NOMOR 46 TAHUN 2023 DALAM PENCEGAHAN DAN PENANGANAN KEKERASAN DI SMA NEGERI 1 MANYAR - Safitri, Ariyanti; Raden Roro Nanik Setyowati (Universitas Negeri Surabaya (Unesa), 2025)
Violence within educational institutions continues to be a significant problem in Indonesia, as it not only hampers the teaching and learning process but also infringes upon students’ rights to receive an education that is safe, comfortable, and respectful of their dignity. In response to this issue, the Ministry of Education, Culture, Research, and Technology enacted Regulation No. 46 of 2023 concerning the Prevention and Handling of Violence in Educational Environments. This study aims to explore how this regulation is implemented at SMA Negeri 1 Manyar, a prominent senior high school in Gresik Regency with a large and diverse student population. The research adopts a descriptive qualitative approach, collecting data through interviews, observations, and documentation. Data analysis is based on George C. Edward III’s policy implementation model, which includes four components: communication, resources, disposition, and bureaucratic structure. The findings reveal that SMA Negeri 1 Manyar has carried out the policy through the development of standard operating procedures (SOPs), the formation of a violence prevention team, the organization of awareness-raising activities, objective handling of reports, and regular monitoring. Despite these efforts, several challenges remain, such as the lack of a dedicated reporting mechanism and limited active participation from all members of the school community. Keywords: School Violence, Policy Implementation, Ministry of Education Regulation No. 46 of 2023.